DEVELOPMENT OF AN EXPERIMENTAL COMPLEX for VERIFICATION AND CALIBRATION OF measuring tools OF Hemodynamics PARAMETERS BASED ON bioimpedance changes - Левицкий, Сергей; Шевченко, Константин (SWorldJournal, 2021)
An article describes research of conditions and development of an experimental complex for check and calibration of measuring devices of parameters of the central hemodynamics on the basis of bioimpedance changing. The most promising and widely used meth